A prescription for exercise in systemic lupus erythematosus. (December 2021) - Molina, Emily; Petri, Michelle; Manno, Rebecca; Williamson, Luke; Williamson, Lyn; Timlin, Homa
Patients with systemic lupus erythematosus (SLE) have increased cardiovascular risk, and fatigue is a major subjective complaint. Sedentary lifestyle has been shown to have negative health impacts in cardiovascular and rheumatic disease, though exercise has not traditionally been incorporated into routine therapy recommendations. Regular exercise in SLE may improve difficult to treat Type 2 symptoms, such as fatigue, depression, stress, and quality of life. Insufficient counseling on exercise by physicians is a notable barrier for SLE patients to engage in physical activity. Aerobic exercise regimens are more commonly studied, and have been shown to improve cardiovascular health in SLE. Exercise may improve some inflammatory markers, though does not definitively affect SLE clinical disease activity. Physical activity should be recommended to improve quality of life and cardiovascular health in patients with SLE. Developing clearer guidelines for exercise regimens in a patient-centered manner is warranted, especially given diverse phenotypes of SLE patients and varying degrees of physical limitations.